Primary graft dysfunction attenuates improvements in health‐related quality of life after lung transplantation, but not disability or depression. Issue 2 (5th September 2020) - Kolaitis, Nicholas A.; Gao, Ying; Soong, Allison; Greenland, John R.; Hays, Steven R.; Golden, Jeffrey; Leard, Lorriana E.; Shah, Rupal J.; Kleinhenz, Mary Ellen; Katz, Patricia P.; Venado, Aida; Kukreja, Jasleen; et al.
Abstract : Disability, depressive symptoms, and impaired health‐related quality of life (HRQL) are common among patients with life‐threatening respiratory compromise. We sought to determine if primary graft dysfunction (PGD), a syndrome of acute lung injury, attenuates improvements in patient‐reported outcomes after transplantation. In a single‐center prospective cohort, we assessed disability, depressive symptoms, and HRQL before and at 3‐ to 6‐month intervals after lung transplantation. We estimated the magnitude of change in disability, depressive symptoms, and HRQL with hierarchical segmented linear mixed‐effects models. Among 251 lung transplant recipients, 50 developed PGD Grade 3. Regardless of PGD severity, participants had improvements in disability and depressive symptoms, as well as generic‐physical, generic‐mental, respiratory‐specific, and health‐utility HRQL, exceeding 1‐ to 4‐fold the minimally clinically important difference across all instruments. Participants with PGD Grade 3 had a lower magnitude of improvement in generic‐physical HRQL and health‐utility than in all other participants. Among participants with PGD Grade 3, prolonged mechanical ventilation was associated with greater attenuation of improvements. PGD remains a threat to the 2 primary aims of lung transplantation, extending survival and improving HRQL. Attenuation of improvement persists long after hospital discharge. Future studies should assess if interventions can mitigate the impact of PGD on patient‐reported outcomes. Abstract : A prospective cohort of lung transplant recipients shows that the development of primary graft dysfunction attenuates improvements in physical health–related quality of life and health utility. See an editorial from Neely et al. on page 456 .